Population pharmacokinetics of vedolizumab in Asian and non-Asian patients with ulcerative colitis and Crohn’s disease - Okamoto, Hiroyuki (Intest Res, 2021)
BACKGROUND/AIMS: Vedolizumab is indicated for moderately-to-severely active ulcerative colitis (UC) and Crohn’s disease (CD). Because multiple factors may result in different pharmacokinetics and clinical efficacies, understanding determinants of vedolizumab clearance may enhance dose and treatment strategies. The aim was to characterize vedolizumab pharmacokinetics in Asian and non-Asian UC and CD patients. METHODS: Population pharmacokinetic analysis for repeated measures, using data from 5 studies, was conducted using nonlinear mixed-effects modeling. A Bayesian estimation approach in NONMEM 7.3 was utilized to leverage the predominantly sparse data available for this analysis with results from a prior population pharmacokinetic analysis of vedolizumab. RESULTS: Vedolizumab pharmacokinetics were described by a 2-compartment model with parallel linear and nonlinear elimination. Using reference covariate values, linear elimination half life of vedolizumab was 24.7 days for anti-vedolizumab antibody (AVA)-negative patients and 18.1 days for AVA-positive patients; linear clearance (CL(L)) was 0.165 L/day for AVA-negative patients and 0.246 L/day for AVA-positive patients; central (V(c)) and peripheral compartment volumes of distribution were 3.16 L and 1.84 L, respectively. Interindividual variabilities (percent coefficient of variation) were 30.8% for CL(L) and 19% for V(c); interoccasion variability on CL(L) was 20.3%; residual variance was 17.8%. For albumin, body weight and AVA, only extreme values were identified as potentially clinically important predictors of CL(L). The effect of race (Asian/non-Asian) and diagnosis (UC/CD) on CL(L) was negligible and likely not of clinical importance. CONCLUSIONS: Pharmacokinetic parameters were similar in Asian and non-Asian patients with moderately-to-severely active UC and CD. This analysis supports use of vedolizumab flat-fixed dosing in these patients. (Clinicaltrials.gov Identifiers: NCT00783718 (GEMINI 1); NCT00783692 (GEMINI 2). CCT 101; NCT02039505 and CCT-001; NCT02038920)